Integrating urban building information modeling and circular economy framework for green sustainability - N. Andriyani; P. Suprobo; T.J.W. Adi; W.A.N. Aspar; A.D. Jatmiko; A.D. Santoso (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The conventional disposal of demolition waste in landfills poses significant ecological harm. Integrating principles of the circular economy can help alleviate this impact by encouraging the reuse, recycling, and recovery of materials. This study presents a groundbreaking approach to demolition that aims to tackle the growing waste problem and bridge the existing regulatory loopholes. The framework leverages Building Information Modeling for Just-In-Time delivery and circular economy practices to prioritize environmentally friendly, efficient, and sustainable operations. The framework aims to transform demolition practices, reduce environmental impact, and promote sustainability within the construction sector by incorporating these principles.METHODS: The study outlines a plan for demolishing high-rise buildings by incorporating Building Information Modeling, Just-In-Time delivery, and the circular economy in a specific case analysis. Autodesk Revit streamlines waste estimation and inventory of reusable, repairable, refurbished, and recyclable waste, thereby optimizing waste management planning with improved effectiveness and efficiency. Navisworks visualizes the demolition process in a reverse four-dimensional model. Microsoft Project ensures on-time delivery, while a Sankey diagram visually represents the concept of a circular economy.FINDINGS: Building information modeling, just-in-time delivery, and circular economy principles maximize demolition planning for efficiency, effectiveness, and sustainability. The green demolition framework serves as a valuable project management tool that enhances planning and resource allocation efficiency, all the while reducing environmental impact through the implementation of selective demolition and enhanced waste management practices.The process completed the demolition of a 6-story building in 88 days, producing 160 cubic meters of reusable waste, eight cubic meters of repairable and refurbishable waste, and 3,972 cubic meters of recyclable wasteThe waste collection for the circular economy is efficiently carried out within a timeframe of 1-2 days, thanks to the implementation of the Just-In-Time delivery schedule.CONCLUSION: This study delves into advancements in waste management and strategic demolition scheduling. The government should consider the green demolition framework when refining regulations to include Information Communication Technologies and circular economy concepts. Future studies have the potential to improve the green demolition framework by prioritizing environmentally conscious strategies and ensuring effective coordination among all stakeholders involved to achieve the best possible outcomes in demolition projects.